EVALUASI KINERJA PORTOFOLIO ANTARA SAHAM SYARIAH DENGAN SAHAM KONVENSIONAL DI BURSA EFEK INDONESIA - Noviastuty, Ari (Performance, 2011)
Efficient portfolio is achieved by combining several securities with the right proportions that maximize return and minimize risk. Optimal portfolio even advisable formed to know the best one stock alternatives, are next to be done that portfolio performance estimation so that investors can know whether the investments made to line with expectations. The results of this research are, there was no differences optimal portfolio stock return based on single index model between index Kompas100 with LQ45, There was no difference in the optimal portfolio on stock return based single index model between Kompas100 index with JII index, There was no difference in the optimal portfolio stock return based on single index model between the LQ45 index with JII index, Performance Optimum portfolio of shares JII not better than the Compass 100 and LQ45.